Evidence-Based Practical Guidance for the Antithrombotic Management in Patients With Coronavirus Disease (COVID-19) in 2020 - Ramacciotti, Eduardo; Macedo, Ariane Scarlatelli; Biagioni, Rodrigo Bruno; Caffaro, Roberto Augusto; Lopes, Renato Delascio; Guerra, João Carlos; Orsi, Fernanda Andrade; Marques, Marcos Areas; Tafur, Alfonso J.; Caprini, Joseph A.; Nicolaides, Andrew; Carter, Charles A.; et al. (Clinical and applied thrombosis/hemostasis, 2020)
This practical guidance, endorsed by the Brazilian Society of Thrombosis and Hemostasis and The Brazilian Society of Angiology and Vascular Surgery, the International Union of Angiology and the European Venous Forum, aims to provide physicians with clear guidance, based on current best evidence-based data, on clinical strategies to manage antithrombotic strategies in patients with coronavirus disease 2019.